Penggunaan E-Commerce, Sistem Informasi Akuntansi, Budaya Organisasi, dan Kinerja UMKM - Dewi, Dewa Ayu Sri Laksmi; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
Performance describes the success of business entities, especially Micro, Small and Medium Enterprises (MSMEs). The research aims to obtain empirical evidence of the effect of the use of e-commerce, accounting information systems, and organizational culture on the performance of MSMEs in Denpasar City. The research population is MSMEs that use e-commerce in Denpasar City with a total population of 665 business units. The sampling method uses probability sampling with simple random sampling technique. The number of samples is 100 samples. Data collection was carried out by distributing questionnaires and analyzed using the SEM-PLS tool. The results showed that the use of e-commerce, accounting information systems, and organizational culture had a positive and significant effect on the performance of SMEs. Keywords: E-Commerce; Accounting Information System; Organizational Culture; MSMEs Performance.